Anatomy of labyrinthine artery and its clinical significance in neurosurgical procedures - A narrative review - Jonasz Tempski; Grzegorz Fibiger; Katarzyna Majka; Ignacy Jastrzębski; Oliwia Andrasz; Dominik Łazarz; Jakub Pękala; Konrad Malinowski; Marcin Czternastek (Translational Research in Anatomy)
The labyrinthine artery (LA), is a major vessel responsible for blood supply of labyrinth and cochlea in the inner ear, as well as cranial nerves, including vestibulocochlear and facial nerves. Its origin varies throughout numerous reports, however the most commonly reported origins include anterior inferior cerebellar artery (AICA) and basilar artery (BA). Nevertheless, arteries such as superior cerebellar, vertebral and posterior inferior cerebellar artery have also been reported as the sources of LA. What is more, the relationship between LA and vestibulocochlear and facial nerves has been described vaguely in many publications. The aforementioned not only represent anatomical idiosyncrasies, but the area of LA origin is also crucial from a clinical perspective, especially when performing a wide spectrum of skull base approaches, most commonly involving exposure of cerebellopontine angle. The thorough knowledge regarding LA course, branches, correlation with cranial nerves can be critical in prevention of iatrogenic lesions, which may occur during various approaches such as middle cranial fossa, rectosigmoid and labyrinthine (both trans- and retro) ones. Lastly, we should remember that many different variants of LA can lead to a broader range of symptoms in the case of vascular changes, such as aneurysms.This publication's aim is to provide a brief overview on all possible variants of labyrinthine arteries described in the literature, as well as its trajectories in relation to vestibulocochlear and facial nerves.